Radio als Hör-Spiel-Raum Medienreflexion - Störung - Künstlerische Intervention - Wodianka, Bettina (Medien- und Gestaltungsästhetik, 2018)
The audio plays of broadcasting history discussed in this book explore opportunities between (particularly technical) dispositive and radio-phonetic forms of performance and staging.